Prevalence of groundnut dry root rot (Macrophomina phaseolina (Tassi) Goid.) and its pathogenic variability in Southern India - Pamala, Prince Jayasimha; Jayalakshmi, R. Sarada; Vemana, K.; Naidu, G. Mohan; Varshney, Rajeev K.; Sudini, Hari Kishan (Frontiers in Fungal Biology, 2023)
Macrophomina phaseolina is the most devastating and emerging threat to groundnut production in India. Due to increase in average temperature and inconsistent rainfalls resultant of changing climatic conditions are strongly believed to aggravate the disease and causes severe yield losses. The present study aims to conduct a holistic survey to assess the prevalence and incidence of dry root rot of groundnut in major groundnut growing regions of Southern India viz. Andhra Pradesh, Telangana, Karnataka, and Tamil Nadu. Further, the pathogenic variability was determined using different assays such as morphological, cultural, pathogenic, and molecular assays. In our study, results revealedResults indicate that disease incidence in surveyed locations ranged from 8.06 to 20.61 per cent. Both temperature and rainfall played a major role in increasing the disease incidence. The pathogenic variability of M. phaseolina isolates differed significantly, based on per cent disease incidence induced on cultivars JL-24 and K-6 of groundnut.Morphological variations in terms of growth pattern, culture colour, sclerotia number and sclerotia size were observed. The molecular characterization of M. phaseolina isolates done by ITS rDNA region using ITS1 and ITS4 primers, yielded approximately 600 bp PCR amplicons, sequenced and deposited in GenBank (NCBI). Molecular variability analysis using SSR primers indicated the genetic variation among the isolates collected from different states. The present investigation revealed that significant variations in pathogenic variability among isolates of M. phaseolina and these may be considered important in disease management and development of resistant cultivars against groundnut dry root rot disease.